2021
DOI: 10.3390/cancers13205174
|View full text |Cite
|
Sign up to set email alerts
|

The Current Landscape of NKT Cell Immunotherapy and the Hills Ahead

Abstract: NKT cells are a specialized subset of lipid-reactive T lymphocytes that play direct and indirect roles in immunosurveillance and anti-tumor immunity. Preclinical studies have shown that NKT cell activation via delivery of exogenous glycolipids elicits a significant anti-tumor immune response. Furthermore, infiltration of NKT cells is associated with a good prognosis in several cancers. In this review, we aim to summarize the role of NKT cells in cancer as well as the current strategies and status of NKT cell i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 229 publications
(377 reference statements)
1
37
0
Order By: Relevance
“…One of the barriers our proposed platform addresses is the difficulty of recruiting peripheral iNKT cells to the tumor site [ 36 ]. Tumor signaling induces the downregulation of iNKT cell IFN-γ secretion relative to immunosuppressive IL-4 cytokine, suppressing tumor infiltration to evade iNKT anti-tumor cytotoxicity [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the barriers our proposed platform addresses is the difficulty of recruiting peripheral iNKT cells to the tumor site [ 36 ]. Tumor signaling induces the downregulation of iNKT cell IFN-γ secretion relative to immunosuppressive IL-4 cytokine, suppressing tumor infiltration to evade iNKT anti-tumor cytotoxicity [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown a relationship between the number and activity of iNKT cells and clinical outcomes, making these cells an interesting therapeutic tool against cancer development and metastasis ( 99 , 101 ).…”
Section: Overview Of Nsclc Tumor Immune Microenvironmentmentioning
confidence: 99%
“…In hematological setting, CAR-γδ T cells showed the ability to cross-present tumor antigens to αβ T cells in vitro, as well as antigen-dependent and independent cytotoxicity. More recently, the feasibility and antitumor activity of allogeneic Vδ1, the subset more frequent within TIL, was reported in a mouse model of hepatocellular carcinoma [ 66 ], and a similar approach is now undergoing clinical trial testing [ 65 ].…”
Section: The Cells To Engineermentioning
confidence: 99%